2018
DOI: 10.3389/fpsyg.2018.00034
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Types of Attention and Auditory Processing Skills: Reconsidering Auditory Processing Disorder Diagnosis

Abstract: Measures of attention have been found to correlate with specific auditory processing tests in samples of children suspected of Auditory Processing Disorder (APD), but these relationships have not been adequately investigated. Despite evidence linking auditory attention and deficits/symptoms of APD, measures of attention are not routinely used in APD diagnostic protocols. The aim of the study was to examine the relationship between auditory and visual attention tests and auditory processing tests in children wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 49 publications
1
35
0
Order By: Relevance
“…After accounting for the influence of short-term memory, simultaneous segregation (diotic performance), and RME, only 16% of the variation in DDdT FR total z-scores can be attributed to the ability to separate different signals at each ear (dichotic processing). Although the clinical data analyzed for this study did not include a test of attention, this factor was found to be associated with variation in dichotic scores in Cameron et al (2016b) and in Stavrinos et al (2018), and cannot be ruled out as an additional variable contributing to dichotic test performance.…”
Section: Hypotheses From Study Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…After accounting for the influence of short-term memory, simultaneous segregation (diotic performance), and RME, only 16% of the variation in DDdT FR total z-scores can be attributed to the ability to separate different signals at each ear (dichotic processing). Although the clinical data analyzed for this study did not include a test of attention, this factor was found to be associated with variation in dichotic scores in Cameron et al (2016b) and in Stavrinos et al (2018), and cannot be ruled out as an additional variable contributing to dichotic test performance.…”
Section: Hypotheses From Study Resultsmentioning
confidence: 89%
“…As detailed in the introduction to Cameron et al (2016a), a number of recent studies have not only reported significant correlations between dichotic performance and cognitive ability but also cast doubt on the interpretation of uncharacteristic right-ear advantage (REA) scores as impaired conduction properties of specific auditory pathways. Instead, it is suggested results can be explained in terms of dynamic processes, including those in which individuals deliberately direct their attention in different ways (Westerhausen and Hugdahl, 2008;Hiscock and Kinsbourne, 2011;Cameron et al, 2016a,b;Stavrinos et al, 2018). Because of the wide use of dichotic tests around the world and the ongoing questions raised in respect to efficacy, the Dichotic Digits difference Test (DDdT; Cameron et al, 2013) was developed to investigate the relationship between dichotic processing and cognitive abilities via the use of differential test scores.…”
Section: Introductionmentioning
confidence: 99%
“…In both PPS and DPS, working memory is loaded with sensory information, i.e., pitch and duration respectively, rather than verbal as in the case of Digit Span, and this kind of information is not processed in the same way in working memory (Wilsch and Obleser, 2016). Furtherly, sensory, rather than verbal processing correlating with impairments in APD children (here deficit in rhythm effects), fits better with the view that APD concerns mainly impairments in lower levels of auditory perception and less with cognition (American Speech-Language-Hearing Association [ASHA], 2005; American Academy of Audiology [AAA], 2010;Stavrinos et al, 2018;Sidiras et al, 2019).…”
Section: Rhythm Effect Vs Auditory Processing and Cognitionmentioning
confidence: 93%
“…Particularly, the core interest of this study is how these effects differ in APD children compared to typically developing ones, and whether they correlate with auditory processing as measured in everyday clinic practice and cognition. In particular, we tested auditory working memory and auditory attention, as these processes have been linked to auditory processing (Weihing et al, 2014;Iliadou et al, 2018;Stavrinos et al, 2018). As the purpose of this study is not to investigate the relation of cognition in general and APD, we limited assessment of cognition to these specific measures.…”
Section: Introductionmentioning
confidence: 99%
“…Cameron, Glyde, Dillon and Whitfield () reported significant correlations between dichotic listening performance and cognitive measures of attention and memory in children with dichotic or memory deficits. Furthermore, new research showed that APD diagnosed individuals may demonstrate attention deficits focused on the auditory modality and limited to a subgroup (Stavrinos, Iliadou, Edwards, Sirimanna & Bamiou, ). From a management point of view, it is well founded that untreated auditory processing deficits have a great negative impact on everyday lives of children (Bamiou, Musiek & Luxon, ) and adults (Atcherson, Nagaraj, Kennett & Levisee, ).…”
Section: Introductionmentioning
confidence: 99%